2010
DOI: 10.1177/0310057x1003800404
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Levels of Local Anaesthetic after Intra-Peritoneal Application – a Systematic Review

Abstract: There is a lack of cohesive reports on the systemic levels of local anaesthetic after intraperitoneal application. A comprehensive systematic review with no language restriction was conducted. Eighteen suitable articles were identified. Data were compiled and presented according to local anaesthetic agent. Intraperitoneal local anaesthetic has been studied in many different procedures, including open and laparoscopic surgery. A total of 415 patients were included for analysis. There were no cases of clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 78 publications
(122 reference statements)
3
37
0
2
Order By: Relevance
“…In humans, the mean maximum concentration after IP administration of bupivacaine is within the range of 0.29 to 1.14 µg/mL for doses of 1.5 to 2 mg/kg and when using bupivacaine concentrations between 0.15% and 0.75%. 3 Peak plasma concentrations in the present study were approximately onethird the concentration that has been reported to cause a convulsive electroencephalogram pattern in cats (3.6 ± 0.7 µg/mL) 26 and approximately oneseventh the concentration required to cause arrhythmias (7.5 to 10.9 µg/mL). 27 A convulsive electroencephalogram pattern and hypotension have been reported for cats at higher plasma concentrations (17 and 21 to 23 µg/mL, respectively).…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…In humans, the mean maximum concentration after IP administration of bupivacaine is within the range of 0.29 to 1.14 µg/mL for doses of 1.5 to 2 mg/kg and when using bupivacaine concentrations between 0.15% and 0.75%. 3 Peak plasma concentrations in the present study were approximately onethird the concentration that has been reported to cause a convulsive electroencephalogram pattern in cats (3.6 ± 0.7 µg/mL) 26 and approximately oneseventh the concentration required to cause arrhythmias (7.5 to 10.9 µg/mL). 27 A convulsive electroencephalogram pattern and hypotension have been reported for cats at higher plasma concentrations (17 and 21 to 23 µg/mL, respectively).…”
Section: Discussionsupporting
confidence: 47%
“…In human medicine, serum concentrations of bupivacaine after IP administration were higher in individuals undergoing laparoscopic cholecystectomy, compared with concentrations in patients receiving a similar dose of bupivacaine and undergoing laparoscopic ovariohysterectomy. 3 This may have been attributable to the extent of dissection and tissue surface area that could have increased the absorption rate. 3 Studies are also warranted to assess the effects of epinephrine on systemic absorption of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After intraperitoneal administration of ropivacaine at doses varying from 100 to 300 mg, her mean Cmax ranged from 0.66 to 3.76 μg/mL and mean Tmax ranged from 15 to 35 minutes. 2 Using ropivacaine, Griffiths et al 3 reported a mean serum concentration of 2.54 mg/mL, 30 minutes after an injection of 3 mg/kg of ropivacaine during a bilateral TAP block. While our ropivacaine dose of 5.2 mg/ kg used for TAP block was higher, it was still within French guidelines which recommend a maximum dose…”
Section: Discussionmentioning
confidence: 99%